BULUREJO-BANYUWANGI VILLAGE FUND POSTULATE AS SUPPORTING THE EFFECTIVENESS OF EMPOWERING PRE-PROSPEROUS COMMUNITIES: POSTULAT DANA DESA BULUREJO-BANYUWANGI SEBAGAI PENUNJANG EFEKTIVITAS PEMBERDAYAAN MASYARAKAT PRA-SEJAHTERA - Iqbal Ramadan; Hary Priyanto; Herwin Kurniadi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The existence of Village Funds is useful for improving public services, alleviating poverty, advancing the village economy, overcoming development gaps, and strengthening village communities as subjects of development. This research aims to determine, describe and analyze the use of Village Funds for empowerment programs for underprivileged communities in Bulurejo Village. Based on the analysis of research findings, the empowerment program supported by the Village Fund directly and indirectly provides stimulus to improve the economy. Recommendations for the use of Village Funds for empowerment programs for underprivileged communities focus on aspects of empowerment problems, identification of community responses, selection of empowerment policy options, and implementation of the use of Village Funds.